2014
DOI: 10.1155/2014/396597
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Hollow Square Sections under Compression Using FRP Composites

Abstract: The feasibility study on carbon fibre reinforced polymer (CFRP) fabrics in axial strengthening of hollow square sections (HSS) was investigated in this paper. CFRP was used as strips form with other parameters such as the number of layers and spacing of strips. Experimental results revealed that the external bonding of normal modulus CFRP strips significantly enhanced the load carrying capacity and stiffness of the hollow sections and also reduced the axial shortening of columns by providing external confineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Secondly, on cold formed lipped steel channel sections strengthened with CFRP, both experimental and analytical study were conducted and the test results revealed that, the load carrying capacity of strengthened specimens were increased by 16.75%. In 2014, to authenticate the estate of CFRP in hollow steel structures, M C Sundarraja et al [1] went through a series of experiments and analytical study in the axial behavior of hollow square steel sections strengthened with CFRP. By changing the parameters such as width of CFRP strips, number of layers they studied the confinement of CFRP strips in the strengthening of hollow steel sections.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, on cold formed lipped steel channel sections strengthened with CFRP, both experimental and analytical study were conducted and the test results revealed that, the load carrying capacity of strengthened specimens were increased by 16.75%. In 2014, to authenticate the estate of CFRP in hollow steel structures, M C Sundarraja et al [1] went through a series of experiments and analytical study in the axial behavior of hollow square steel sections strengthened with CFRP. By changing the parameters such as width of CFRP strips, number of layers they studied the confinement of CFRP strips in the strengthening of hollow steel sections.…”
Section: Related Workmentioning
confidence: 99%
“…Steel structure being structurally sound such as high strength-to weight ratio, long durability, less weight, huge energy consumption capacity, high torsional austerity and so other factors. In recent times, the economical gratifications have also been identified by the engineers and the designers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research conducted in this area has focused on three parts: firstly, retrofit the beam with CFRP, including reinforcing damaged steel beams [3,9,10,12,16] and undamaged steel beams [4,5,14]. These works show that the ultimate load capacity of steel beams was improved after reinforced with CFRP; secondly, using CFRP to reinforce the axial compressive steel members [6,8,11,13,15,19,21], the reinforced specimen section includes the T, H, circular and square tube section. These literatures indicate that the CFRP can improve the flange and web local buckling or flexural torsional buckling load capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The composites, which are light in weight, high in strength, and can be manufactured according to the required performance, have been accepted in industrial fields. With the rapid development of aerospace, composites have been one of the four structural materials after aluminum, steel, and titanium materials . At present, both the macro‐ and micro‐mechanical methods are used to analyze the mechanical behaviors of composite structures .…”
Section: Introductionmentioning
confidence: 99%